Beyond MAP: A guide to dimensions of rainfall variability for tropical ecology. (6th September 2020) - Schwartz, Naomi B.; Lintner, Benjamin R.; Feng, Xue; Powers, Jennifer S.
Abstract: Tropical ecologists have long recognized rainfall as the key climate filter shaping tropical ecosystem structure and function across space and time. Still, tropical ecologists have historically had a limited toolkit for characterizing rainfall, largely relying on simple metrics like mean annual precipitation (MAP) and dry season length to characterize rainfall regimes that vary along many more dimensions. Here, we review methods for quantifying dimensions of rainfall variability on multiple time scales, with a focus on ecological applications of these methods. We also discuss key considerations for tropical ecologists looking to use rainfall metrics that better align with hypothesized biological or ecological mechanisms or that more effectively describe rainfall variability in the systems we study and provide a toolkit (R scripts and gridded datasets) to do so. We argue that incorporating more sophisticated approaches to quantify rainfall variability into study design and statistical analyses will enhance our understanding of past, ongoing, and future changes in tropical ecosystems. Abstract in Spanish is available with online material. Resumen: Durante mucho tiempo en la ecología tropical se ha considerado que la variabilidad de la lluvia representa un filtro ambiental que determina la distribución, estructura y función de los ecosistemas tropicales en el espacio y en el tiempo. Sin embargo, históricamente se han utilizado un número limitado de variables, como la precipitación media anual (PMA) y la duración de la estación seca para caracterizar como la lluvia varía a través de sus múltiples dimensiones. En el presente artículo se revisan diferentes métodos para cuantificar la variabilidad de la lluvia a través de escalas temporales, haciendo énfasis en sus aplicaciones metodológicas. Adicionalmente, sugerimos puntos claves para el uso de métricas que mejoran la predicción de procesos biológicos y ecológicos. Estas métricas describen de una mejor manera la variabilidad de la lluvia en los ecosistemas tropicales, para su implementación proveemos códigos de R y datos en raster. Finalmente, proponemos que la incorporación de métricas más sofisticadas para cuantificar la variabilidad de las precipitaciones mejorará nuestra comprensión de los cambios que han experimentado y experimentarán los ecosistemas tropicales.